Stroke associated with non-adherence and non-persistence with direct oral anticoagulants in Germany. (24th May 2021) - Smits, E; Holthuis, E; Enders, D; Spentzouris, G; Beier, D
Abstract: Funding Acknowledgements: Type of funding sources: Other. Main funding source(s): Daiichi Sankyo Europe GmbH Background: Based on results of multiple randomised controlled trials, direct oral anticoagulants (DOACs) are frequently used to reduce stroke risk in patients with atrial fibrillation (AF). The hypothesis is that in the real-world setting DOACs are effective in reducing the risk of stroke but ensuring continuous use is essential because of the rapid decline in anticoagulation activity when doses are omitted. Purpose: The aim of this study was to assess the relationship between non-adherence, discontinuation of DOAC treatment and incidence of ischaemic stroke. Methods: A nested case-control study was conducted in the InGef database, an anonymised healthcare claims database in Germany. AF patients starting DOACs between drug approval date and 31/12/2018 were included. We restricted to patients aged ≥45, ≥1 year database history, ≥1 year follow-up and at least two DOAC dispensings after cohort entry date (CED) (date of first dispensing). Patients with an ischaemic stroke during follow-up were selected as cases and compared with matched controls (matched on age +/- 5 years, sex, year of CED and CHA₂DS₂-VASc-score at CED). Controls were assigned the index date (date of first stroke diagnosis) of the corresponding case. Adherence to treatment was assessed among current users (DOAC use at or within 30 days before index date) and defined as proportion of days covered (PDC) ≥80% during CED and index date. Persistent users were defined as those with continuous DOAC use from CED to index date. We also assessed the effect of current, recent (DOAC use within 30-365 days before index date) and past use (DOAC use more than 1 year before index date). Odds ratios (ORs) with 95% confidence intervals (CIs) for ischaemic stroke were determined in logistic regression models. Results: 900 cases and 3, 570 controls were included. Among cases and controls, mean ± sd age was 80 ± 8 years and 49% were male. Current users who were non-adherent had a significant 1.21 higher odds (95% CI 1.01-1.45) of ischaemic stroke compared to adherent users. Similar results were observed in twice-daily (BID) users (OR 1.42 (1.15-1.75)). However, among once-daily (QD) users, the odds was not different between the adherent and non-adherent users (OR 0.99 (95% CI 0.58-1.69)). The risk of ischaemic stroke was significantly higher among non-persistent users compared to persistent users (OR 1.91 (95% CI 1.64-2.22)). Similar findings were observed among QD and BID users. The comparison of past and recent users to current users showed that the OR became higher the longer a patient had stopped DOAC use. Conclusion: Both non-adherence and non-persistence were found to increase the risk of ischaemic stroke, showing that continuous use is essential for both BID and QD users. In BID users, there seems to be a stronger association between non-adherence and risk of stroke than in QD users. An explanation might be the higher degree of difficulty in adhering to a BID than QD regimen.